PEDAGOGICAL FEATURES OF FORMING MILITARY SKILLS IN FUTURE MILITARY SERVANTS (ResearchJet Journal of Analysis and Inventions, 2023)
This article presents an analysis of data on the important factors of military skill formation in future military personnel. Also, the definition of pedagogical conditions of military skills, problems and theoretical interpretation of evaluation methods are highlighted.